2011
DOI: 10.1099/ijs.0.026146-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium pseudoryzae sp. nov., isolated from the rhizosphere of rice

Abstract: A Gram-stain-negative, aerobic, rod-shaped bacterium, designated strain J3-A127 T , was isolated from the roots of fresh rice plants (Oryza sativa). Cells were non-motile and no flagellum was detected. Comparison of 16S rRNA gene sequences indicated that the strain was phylogenetically related to species of the genus Rhizobium, with closest similarity to Rhizobium oryzae Alt 505 T (96.4 %). The low levels of 16S rRNA gene sequence similarity (,90 %) found between the gyrB, atpD, recA and glnII gene sequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Root tissue (5 g) was used to isolate the endophytes according to the previously described methods of Zhang et al (2011). Routine cultivation of strain ZYY112 T was performed with R2A agar (Difco) or trypticase soy agar (TSA; Difco) medium adjusted to pH 7.0 at 28 8C.…”
mentioning
confidence: 99%
“…Root tissue (5 g) was used to isolate the endophytes according to the previously described methods of Zhang et al (2011). Routine cultivation of strain ZYY112 T was performed with R2A agar (Difco) or trypticase soy agar (TSA; Difco) medium adjusted to pH 7.0 at 28 8C.…”
mentioning
confidence: 99%
“…In addition, some type strains of the genus Rhizobium were also negative for nodulation in recent studies. Rhizobium pseudoryzae J3-A127 T , isolated from the roots of rice plants Oryza sativa, did not form any nodules on four different legumes, and the nodD and nifH genes were not detected by PCR (Zhang et al, 2011). Rhizobium soli DS-42 T neither forms nodules nor is confi rmed to have the nodD and nifH genes (Yoon et al, 2010).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Strain F11 T had a similar cellular fatty acid profi le to its closest neighbors, Rhizobium oryzae Alt 505 T and Rhizobium pseudoryzae J34A-127 T ( Table 2). The major fatty acid of F11 T was C 16:0 (6.24%) and summed feature 8 (C 18:1ω7c and/or C 18:1ω6c , 76.59%), which are typical fatty acids of root-nodule bacteria (Tighe et al, 2000;Zhang et al, 2011).…”
Section: Phenotypic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic leguminous plants have also been reported to harbour species of the genus Rhizobium (Zurdo-Piñeiro et al, 2004). Previous studies showed that novel species of the genus Rhizobium can also be found as endophytes colonizing roots of nonleguminous plants including rice, wheat and maize (Peng et al, 2008;Rosenblueth & Martínez-Romero, 2004;Schloter et al, 1997;Zhang et al, 2011b). Their role in promoting growth of non-leguminous plants has also been proposed (Yanni et al, 1997).…”
mentioning
confidence: 99%